(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the course of recent decades India has set up a scope of laws and projects to address the issue of child labor. UNICEF and its India accomplices are working together to guarantee that children are shielded from work and exploitation which is destructive to their improvement They are working to guarantee that children stay in economically stable family homes and get the chance to go to school and be taught. Child labor can’t be managed in disengagement. It is naturally connected to financial factors. All the more explicitly, UNICEF has likewise started work with employers and the private segment to evaluate and address the impact of their inventory network and business practices on children. In passing the 86th Amendment to the Constitution of India, education is a fundamental right. This has suggestions for satisfaction of the commitment of the State to guarantee that each child is in school. Since most children who don’t go to schools are engaged in some type of work or another, it is fundamental that there is a complete arrangement to pull back children from work and standard them into schools. At the end of the day the labor division has a critical job to abrogate child labor in the entirety of its structures and guarantee that children make the most of their right to education. This is to be sure a difficult assignment, however can be achieved with purposeful exertion and a reasonable point of view. In this article we studied about the child labor and protection of child labor under Indian Constitution.